1999
DOI: 10.1111/j.1745-6622.1999.tb00517.x
|View full text |Cite
|
Sign up to set email alerts
|

When Do Strategic Alliances Create Shareholder Value?

Abstract: This article reports the findings of the authors' study of the stock market reaction to 345 strategic alliances announced during the period 1983-1992. The study reports statistically significant gains that, when translated into dollars, are divided roughly evenly between the larger and smaller partners (though the smaller partners experience larger percentage gains). Moreover, the value gains are largest in those cases in which two high-tech firms ally to develop or apply new technology, while the market shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…For each event window, the cumulative abnormal returns for the firms participating in technology alliances are significant and larger than those participating in marketing alliances. Similar results have also been reported by Chan et al (1999) and Koh and Venkataraman (1991).…”
Section: Technological Versus Marketing Alliances: Why and How Are They Different?supporting
confidence: 91%
See 1 more Smart Citation
“…For each event window, the cumulative abnormal returns for the firms participating in technology alliances are significant and larger than those participating in marketing alliances. Similar results have also been reported by Chan et al (1999) and Koh and Venkataraman (1991).…”
Section: Technological Versus Marketing Alliances: Why and How Are They Different?supporting
confidence: 91%
“…There is empirical evidence consistent with the above argument. Shareholders of firms entering into different types of alliances enjoy varying levels of benefits (Das et al , 1998; Chan et al , 1999). For example, Das et al (1998), show that although announcement of strategic alliances by firms are viewed, on average, as good news by the investors, 49 firms participating in technology alliances had positive and statistically significant abnormal returns in all the event windows, the average abnormal return being 1.63 percent for a three‐day event window.…”
Section: Technological Versus Marketing Alliances: Why and How Are They Different?mentioning
confidence: 99%
“…Some other empirical research focused on particular strategic alliances to test the relationship between strategic alliance announcements and firm performance. For example, Chan and his colleagues (1999) also examined 345 technical and marketing alliances and concluded that the overall average abnormal return is around 0.64%, while the high-technology firms can gain more benefit, amounting to 1.12%, and the overall average abnormal return benefit by technical horizontal alliances and marketing non-horizontal alliances can be even higher, up to 3.5% and 1.45%, respectively [28]. Swaminathan and Moorman (2009) only picked up 230 marketing alliances and found that marketing alliance announcements can create an average abnormal return value of 1.4% [10].…”
Section: Strategic Alliances and Firm Performancementioning
confidence: 99%
“…Chan, Kensinger and Keown (1997) found that stock prices responded positively to the formation of alliances and partnering firms displayed better operating performance than their industry peers over a five-year period. The value of alliances is especially plain to see when the partnerships involve the exchange of technological assets and skills (Chan, Kensinger, Keown and Martin, 1999;Hagedoorn and Schakenraad, 1990). Moreover, in high-technology industries, enterprises leverage alliances to enhance their competitiveness.…”
Section: Theoretical Perspectives On Alliancesmentioning
confidence: 99%